Global Russian cultures - Platt, Kevin M. F., 1967- (The University of Wisconsin Press, 2018)
Vladimir Putin has tried to rationalize the 2014 annexation of Crimea as a defense of the "millions of Russian and russophone people" who live there--an irredentist logic that rests on an understanding of a unified, fixed, primordial "Russian-ness." Challenging this notion of an essential Russian identity that must be kept pure and whole, Global Russian Cultures explores the protean complexity of Russian culture as it has spread across the world through successive waves of migration. "Both within and without the Russian Federation," explains editor Kevin Platt, "Russian culture is fragmented and multiple." In revealing Russian cultures as plural, unbounded, and polycentric, this volume calls into question the exculpatory reasoning that fuels the Russian projection of power and, implicitly, similar imperial projects